On the Pompeiu problem and its generalizations - Volchkov, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
Functions are investigated whose integrals over a given collection of sets are zero. Pompeiu sets are described in terms of the approximation of their indicators by linear combinations of the indicators of balls with special radii.